Anaplastic lymphoma kinase inhibitors in phase I and phase II clinical trials for non-small cell lung cancer. (3rd June 2017) - Karachaliou, Niki; Santarpia, Mariacarmela; Gonzalez Cao, Maria; Teixido, Cristina; Sosa, Aaron E.; Berenguer, Jordi; Rodriguez Capote, Alejandra; Altavilla, Giuseppe; Rosell, Rafael
ABSTRACT: Introduction : Crizotinib is a first-in-class ALK tyrosine kinase inhibitor (TKI), which has proven its superiority over standard platinum-based chemotherapy for the first-line therapy of ALK-rearranged non-small cell lung cancer (NSCLC) patients. The development of acquired resistance to crizotinib represents an ongoing challenge with the central nervous system being one of the most common sites of relapse. Ceritinib and alectinib are approved second-generation ALK TKIs. Several novel ALK inhibitors, more potent and with different selectivity compared to crizotinib, are currently in development. Areas covered : This review will focus on new ALK inhibitors, currently in phase 1 or 2 clinical studies. We will also comment on the mechanisms of resistance to ALK inhibition and the strategies to delay or overcome resistance. Expert opinion : The therapeutic management of ALK-rearranged NSCLC has been greatly improved. Next-generation ALK inhibitors have shown differential potency against ALK rearrangements and ALK resistance mutations. The molecular profile of the tumor at the time of disease progression to crizotinib is crucial for the sequencing of novel ALK TKIs. Ongoing clinical studies will address key issues, including the optimal therapeutic algorithm and whether combinational approaches are more effective than single ALK inhibition for the outcome of ALK-rearranged NSCLC patients.